Facing the challenges of smokeless tobacco epidemic in Bangladesh. Issue 2 (5th March 2022) - Zaman, M Mostafa; Hakim, Ferdous; Alam, Syed Mahbubul; Sujon, Aminul Islam; Banik, Palash Chandra; Bhuiyan, Rijwan; Rahman, Md. Bazlur; Karim, Iftekhairul; Alam, Mashud
Abstract: Background: Smokeless tobacco (SLT) use in Bangladesh is one of the highest in the world. Despite having a tobacco control programme, the use of SLTs has increased in recent years. The objective of this paper is to report on the prevalence of SLTs and challenges faced during control measures in Bangladesh. Methods: A wide range of published reports on tobacco in general and SLT were reviewed. Websites of relevant organizations and national survey reports including PubMed were visited to identify national‐ or subnational‐level data. Legislations, policies and their implementation and programmes are reviewed. Additional data were captured by active surveys on SLT products, especially on graphic health warning. The authors' perspectives on SLT control in Bangladesh were captured through a series of brainstorming sessions. Findings: The reported prevalence of SLTs ranged from 21% to 26% among adults. SLT control measures are not adequately addressed despite the existence of several policies and programmes. It is based to the definition of Tobacco Control ACT in 2013. We propose inadequate prioritization and weak policy directives; unregulated industry leading to high production, marketing, violation of package warning and tax evasion; high level of cultural acceptance; and poor awareness of the people as challenges to the control efforts. In addition, a lenient attitude of the government towards the so‐called "cottage" industry made SLTs unabated. We propose prioritization of SLT control, strengthening industry monitoring and tax measures, countering cultural acceptability and public ignorance and cessation support engaging government and civil society organizations as the way forward. Conclusion: The control measures should be evidence‐based warranting operational research. Government and non‐government organizations' collaborative efforts on an immediate, short‐and long‐term basis are recommended to meet the challenges of SLTs. These primarily include policy support for prioritization, enforcement of legislation, industry and marketing regulation, stringent tax measures, denormalizing societal acceptability and cessation support.